A humanized anti-MSLN×4-1BB bispecific antibody exhibits potent antitumour activity through 4-1BB signaling activation and fc function without systemic toxicity - Da-yan Zhang; Zhi-hua Zhang; Wen-ting Liu; Wei-ming Zhou; Peng-fei Zhou; Juan-juan Wei; Xue-jing Dai; Xiao-li Zeng; Yu-qiong Zhou; Han-wang Li; Heng Zhang; Ao-lin Shen; et al. (Journal of Translational Medicine)
Abstract Background Agonistic monoclonal antibodies targeting 4-1BB/CD137 have shown preclinical promise, but their clinical development has been limited by severe liver toxicity or limited efficacy. Therefore, a safe and efficient immunostimulatory molecule is urgently needed for cancer immunotherapy. Methods A novel anti-MSLN×4-1BB bispecific antibody (bsAb) was generated via antibody engineering, and its affinity and activity were detected via enzyme-linked immunosorbent assay (ELISA), flow cytometry, and T-cell activation and luciferase reporter assays. In vivo antitumour activity was assessed by establishing humanized mice bearing human MSLN-expressing MC38 (MC38/hMSLN) or CT26 (CT26/hMSLN) cells, and safety was further evaluated in cynomolgus monkeys. Results We generated two humanized anti-MSLN×4-1BB bsAbs (HK013-G1/G4) by fusing an anti-4-1BB scFv to the C-terminus of an anti-MSLN VHH with an intact Fc fragment from human IgG1 or IgG4. The two bsAbs were able to block the binding of CA125 to MSLN and stimulate 4-1BB signaling pathway, which was strictly dependent on MSLN expression. In particular, HK013-G1 retained Fc function and induced ADCC effect in tumour cells, whereas HK013-G4 did not. Strikingly, HK013-G1 showed superior antitumour activity to HK013-G4 both in vitro and in vivo and remained effective even in the presence of soluble MSLN. HK013-G1 enhanced antitumour immunity and induced durable antigen-specific immune memory to prevent rechallenged tumour growth, even at a dose as low as 1 mg/kg. Furthermore, HK013-G1 did not induce nonspecific production of proinflammatory cytokines and showed good tolerability up to the highest tested dose (30 mg/kg weekly) for 5 weeks, with no HK013-G1-related adverse effects observed in cynomolgus monkeys. In addition, the mean half-life of HK013-G1 was approximately 61 and 97 h at single doses of 3 and 30 mg/kg, respectively. Conclusion The optimal anti-MSLN×4-1BB bsAb HK013-G1 exhibited synergistic antitumour effects by inducing an ADCC effect (innate immunity) and stimulating the 4-1BB signaling pathway (adaptive immunity) upon cross-bridging with MSLN with no systemic toxicity, which may offer the promise of an improved therapeutic window relative to that of 4-1BB agonists.